O processo de escrita e reescrita: aplicação de sequência didática com o gênero artigo de opinião - Lima, Jocélio de Barros (2023)
It is noted that, among the general competences defined by the National Common Curricular Base (BNCC) of Brazil (2018), which students must develop throughout Basic Education, there is the competence to argue, defend an opinion based on in data and evidence, respecting and considering human rights, in addition to developing a sense of community responsibility, which involves public and social issues. From this perspective, with the aim of achieving these competences, the aim of this work was to analyze the teaching-learning process of writing and rewriting by 8th grade students at a public school in Mari, Paraíba. The research took place through Didactic Sequence, which encourages students to produce opinion articles in the search for writing with a critical position. Therefore, the work is structured by these thematic axes, addressed in the theoretical framework, namely: gender in the conception of Bakhtin (2015) and others; opinion article, based on Bräkling (2008), Rodrigues (2008), Casseb-Galvão and Duarte (2018); teaching writing and rewriting, in the view of Geraldi (2011, 2015, 2017), Kato (2009), Serafim (1995), Ruiz (2020), Menegassi (2001, 2013); argument proposed by Oswaldo Ducrot (1987, 1988), Anscombre/Ducrot (1994) and collaborators; Didactic Sequence with a brief context of theoretical-methodological proposals, according to Dolz, Noverraz and Schneuwly (2011), Zabala (1998), Souza (2018), Oliveira (2013), among others; and, finally, for critical thinking, Lopes et al. (2019). The methodological path was developed through a qualitative research, whose field work was guided by an interventionist action research. The data generation instruments were participant observation (logbook), conversation circle (poll) and Didactic Sequence. In the data analysis, the theoretical-methodological foundations of Dolz, Noverraz and Schneuwly (2011) were adopted, when they deal with the application and analysis of SD from the perspective of Socio-Discursive Interactionism (ISD). As a result, it was demonstrated that DS procedures contributed to the development of writing, as well as social and literacy practices, in addition to critical thinking. Given the above, this work ends with a "Pedagogical Notebook" for teachers of the state network school, in addition to emphasizing that the application of the project significantly improved the writing development of the participating students during the course of the research.